Alloy Substitution in a Critical Raw Materials Perspective - Paolo Ferro; Franco Bonollo; Sylvia Cruz (Fracture and Structural Integrity)
Since many years, the European Community has been monitoring some raw materials because of their high importance to the European Union economy and their high supply risk. Such raw materials, classified as critical, form a strong industrial base, producing a lot of goods and applications used in everyday life and modern technologies. Many critical raw materials are used to produce alloys and their high supply risk may constitute a serious problem for the future world economy and technological progress. Mitigating actions are therefore needed such as recycling, material efficiency improvements and, when possible, material substitution. In the present work, a systematic approach for alloy substitution in a critical raw materials perspective is developed. The method is illustrated with an example.